Principles of public speaking - German, Kathleen (Princeton, New Jersey : Recording for the Blind & Dyslexic, 2003)
This book presents the fundamental principles [to help] students gain the expertise and confidence to speak in public. It combines the latest research of scholars in rhetorical and communication theory with practical advice to students on how to speak effectively in a culturally diverse society .This textbook focuses on communication in your college life but also includes examples from the worlds of work, politics, and social activism.-Pref.
Part1. Public speaking and critical listening -- Part2. Planning and preparing your speech -- Part3. Presenting your speech --Part4. Types of public speaking: Speeches to inform .
Includes index.
Keywords: PUBLIC SPEAKING